The impact of artificial intelligence on enhancing predictive decision-making in Human Resource Management: An empirical analysis within the Tunisian context - Founès, Sofiane; Boudabbous, Sami (International research journal of management, IT and social sciences, 2025)
Across our interconnected world, the incorporation of artificial intelligence (AI) is reshaping how human resource management (HRM) makes its decisions (Amamou Mériam, 2023). In a country like Tunisia, which is committed to becoming a digital society, AI-based analytics is seen as just a starting point for improving HR forecasting and strategic influence, and it comes with inherent socio-cultural issues (Haak-Saheem, W et al., 2024). It is based on this that we turn to examine current research and applications of AI in HRM in Tunisia. We will explore both the factors promoting and those impeding adoption. Further, we critically assess ethical, organizational, and regulatory factors (Muraleedharan NV et al., 2025). Utilizing both new case studies and a comparison of the relevant literature, this article provides helpful guidelines for leveraging predictive HRM specifically within the Tunisian landscape. We highlight key areas such as the value of AI that focuses on human needs (Tembine, H et al., 2024), strong data management, and expanding the skills of the workforce to enable comprehensive growth.